Improving the special physical training of gymnasts in sports aerobics at the initial training stage - Galyna Artemieva; Inna Bodrenkova; Tetiana Moshenska (Kharkiv State Academy of Physical Culture, 2019)
Competition is intensifying on the world platform, competitive activity is becoming more complex, requirements for the performing skills of athletes are being raised, special requirements are being placed on the level of special physical fitness of gymnasts, and it is becoming increasingly difficult to win. There are new problems that leading experts associate with the process of many years of sports training. Now in sports aerobics (aerobic gymnastics) there is the problem of developing special physical qualities of athletes, starting from the initial training stage. Also, the issues of selecting adequate means and methods have not been sufficiently resolved, their rational combination in the training process, taking into account the specificity of the competitive activity of this sport, modern refereeing and tasks of this stage. Purpose: theoretically develop and experimentally substantiate the methodology for improving the special physical training of gymnasts in sports aerobics at the initial training stage. Material & Methods: a complex of scientific research methods (pedagogical research methods and methods of mathematical statistics) was used. 32 athletes (7-8 years old, girls) took part in the experimental part. Two groups were formed (control - 16 girls, and the main - 16 girls). Results: through the use of an experimental technique, selection of funds and the optimal combination of loads, taking into account the age characteristics of young athletes, an increase in physical performance was obtained, the physical and functional preparedness of the gymnasts of the main group increased. Conclusions: the developed methodology for improving the special physical training of gymnasts 7-8 years old, who are engaged in sports aerobics (aerobic gymnastics), ensures the growth of physical capabilities of athletes, solves the main tasks of the training stage, based on the specifics of motor activity, sensitive periods of development of physical qualities in this form sports, contributes to comprehensive physical development, integrated physical preparedness, the laying of a specific functional base for effective of learning technology.